2020
DOI: 10.1055/a-1256-0571
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an internal anchoring plastic stent to prevent migration of a fully covered metal stent in malignant distal biliary strictures: a randomized controlled study

Abstract: Background: Two types of self-expandable metal stents (SEMS) are available for malignant distal biliary obstruction: fully covered SEMS (FCSEMS) and uncovered SEMS. FCSEMS can prevent stent ingrowth, but a major concern is the spontaneous migration. The aim of this study is to determine whether the additional insertion of a double pigtail plastic stent to anchor the FCSEMS can prevent migration. Methods: Sixty-eight patients with unresectable malignant distal biliary obstruction were included in this multicen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 26 publications
(43 reference statements)
0
16
0
Order By: Relevance
“…Before applying doublepigtail stent anchoring of FCSEMSs in general practice, there are several points that need to be clarified. First, the shorter length of the FCSEMSs used in this study may have resulted in a higher migration rate in the non-anchored group, this having been even higher than that for FCSEMSs used in benign lesions, around 5 %-37 % [1,4]. Kogure et al revealed that the stent migration rate in FCSEMSs used for malignant distal biliary obstruction was only 14 % with stent lengths of mostly 6 or 8 cm [3].…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Before applying doublepigtail stent anchoring of FCSEMSs in general practice, there are several points that need to be clarified. First, the shorter length of the FCSEMSs used in this study may have resulted in a higher migration rate in the non-anchored group, this having been even higher than that for FCSEMSs used in benign lesions, around 5 %-37 % [1,4]. Kogure et al revealed that the stent migration rate in FCSEMSs used for malignant distal biliary obstruction was only 14 % with stent lengths of mostly 6 or 8 cm [3].…”
mentioning
confidence: 72%
“…We recently read with interest the article by Paik et al reporting a randomized controlled study that demonstrated that an additional double-pigtail plastic stent anchoring a fully covered self-expandable metal stent (FCSEMS) for malignant biliary obstruction prevented stent migration and prolonged patency without any serious adverse events [1]. International consensus recommends the use of covered metal stents for unresectable malignant distal biliary stricture [2], with stent migration being one of the most concerning adverse events with FCSEMSs [3].…”
mentioning
confidence: 99%
“…Both types of FCSEMS were able to be removed in all of the patients[ 122 ]. Overall, new stent designs including anchoring flaps, flared ends, and additional anchoring plastic stents have been validated in studies to reduce migration risk[ 123 - 125 ].…”
Section: Complicationsmentioning
confidence: 99%
“…Their characteristics and associated adverse events are listed in Table 1. [38][39][40][41][42][43][44][45][46][47][48] These three types of stents are used extensively in practice. There have been limited studies comparing their clinical efficacy and safety, and produced inconsistent results, leaving stent selection a contentious topic.…”
Section: Selection Of Drainage Stentmentioning
confidence: 99%
“…[27] The tube shape of FCSEMS involves a higher migration risk; however, it has been reported that placing a doublepigtail PS in the lumen can immobilize FCSEMS, thereby preventing migration and extending patency time. [40] The double-walled flanges on both ends of LAMS can anchor the position and the self-expansion design with complete silicone covering can avoid leakage along the tract. Besides, because of its large diameter, the LAMS can allow direct endoscopic necrosectomy through the stent if required.…”
Section: Selection Of Drainage Stentmentioning
confidence: 99%